2012
DOI: 10.2174/157488912798842269
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid-related Agents in the Treatment of Anxiety Disorders: Current Knowledge and Future Perspectives

Abstract: Rich evidence has shown that cannabis products exert a broad gamut of effects on emotional regulation. The main psychoactive ingredient of hemp, Δ9-tetrahydrocannabinol (THC), and its synthetic cannabinoid analogs have been reported to either attenuate or exacerbate anxiety and fear-related behaviors in humans and experimental animals. The heterogeneity of cannabis-induced psychological outcomes reflects a complex network of molecular interactions between the key neurobiological substrates of anxiety and fear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 231 publications
(215 reference statements)
2
57
0
1
Order By: Relevance
“…Similar opposing effects were reported for fear-related freezing behavior (Kamprath et al 2009;Lafenêtre et al 2009;Metna-Laurent et al 2012). Furthermore, TRPV1 and CB1 seem to exert opposite effects on fear and anxiety (Marsch et al 2007; for review, see Moreira et al, Neuroscience 2012;Aguiar et al 2014), and also CB2 receptors were reported to modulate anxiety-like behavior (Tambaro and Bortolato 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Similar opposing effects were reported for fear-related freezing behavior (Kamprath et al 2009;Lafenêtre et al 2009;Metna-Laurent et al 2012). Furthermore, TRPV1 and CB1 seem to exert opposite effects on fear and anxiety (Marsch et al 2007; for review, see Moreira et al, Neuroscience 2012;Aguiar et al 2014), and also CB2 receptors were reported to modulate anxiety-like behavior (Tambaro and Bortolato 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic exposure to ⌬ 9 -THC in adolescent rats induces a depressive-like phenotype in adulthood (720,756). In humans, the interindividual variability in the responses to cannabis may depend on a wide spectrum of factors, such as the relative concentrations of ⌬ 9 -THC and other phytocannabinoids (846).…”
mentioning
confidence: 99%
“…This possibility is supported by preclinical evidence in rodents subjected to both acute and chronic administration of METH [105]. However, cannabis has been shown to produce variable effects with respect to anxiety [106] and may even exacerbate some of the negative subjective sensations induced by ATSs, such as panic and paranoia.…”
Section: Interactions Of Cannabis and Atssmentioning
confidence: 91%
“…This scenario suggests that METH neurotoxicity may result in altered responsiveness of CB 1 receptors, possibly due to selective damages of specific subpopulation of neurons and homeostatic imbalances of the endocannabinoid system in the brain areas that regulate the modality and intensity of environmental reactivity, such as amygdala, prefrontal cortex and hippocampus [106,310].…”
Section: Role Of Cannabis In the Outcomes Of Meth Neurotoxicitymentioning
confidence: 99%